Ensino de Ciências e tradição Maxakali: construindo relações em busca de um mundo comum - Katia Pedroso Silveira (2015)
This work results from a long reflection about the teaching of Sciences in a context of training of indigenous teachers from Maxakali ethnic group, located in the northeast of Minas Gerais. My approach to this community allowed me to observe how its interaction with the white world is important and multifaceted for it. In this manner it is both reported my engagement along almost seven years with the Maxakali people and pictured my uneasiness, reflections and investigations in search of a science teaching for this particular context. To this end, I made a bibliographical research about both the origin and history of the Maxakali with the white world and the central ideas of their cosmology. It was also developed a fieldwork in the Indigenous Land Aldeia Verde as well as in urban setting. Viveiros de Castro's anthropological formulation the Amerindian Perspectivism and, especially, the idea of potential affinity was extremely important to understand the Maxakali universe, which enables me to apprehend the political, ritual and cosmological values ascribed by them to the alterity. The school, institution originally occidental, became a space of interchanges between the two worlds, indigenous and occidental. The Maxakali preserve not only their language, but also their chants, myths and rituals. The life in the village is permeated by the relations between the tikm'n how they call themselves and their yãmy the chanting spirits, the great source of the Maxakali knowledge. The relation with the white world promotes the entrance of a set of technological artifacts and benefits which is not always positive. The interaction with the university seems, in the Maxakali view, to be a path to a better understanding about the logic of western thought and its artifacts. It can help them to build a stronger autonomy facing this universe. This exploration of the tikm'n universe and the reflections about a group of science classes that I taught to them in a course of training of indigenous teachers allowed me to suggest a possible approach to the Science teaching in this context. An approach that entails a more symmetric relation between the two knowledge systems. A Science teaching as a creative practice or a creative exercise in Wagner's terms. Science classrooms conceived as relational spaces that promote a two-way anthropological exercise, where the indigenous students seek for a comprehension about the Science, and the Science teachers pursue a better understanding about the Amerindian universe. The Science teaching as a cosmopolitical practice, as a space for the construction of a common world, as suggested by Latour. Finally, an education that accomplish a pluricultural effort, acknowledging the differences between the two ways of rationale, the scientific and the traditional, though respecting and accepting these other ways of exist and know.